Constructing Z‐Scheme Bi2O3/In2O3 Heterojunction for Efficient Photocatalytic Degradation of Rhodamine B. Issue 11 (20th August 2020) - Chen, Hongjun; Wang, Zi; Xue, Zeyang; Yu, Chunhu; Pei, Lizhai; Fan, Chuangang
Abstract: A Bi2 O3 /In2 O3 heterojunction is successfully fabricated via a facile hydrothermal method using sodium bismuthate and indium nitrate as the source materials. The crystal structure, composition, micromorphology, and optical property of the Bi2 O3 /In2 O3 heterojunction are analyzed by X‐ray diffraction, X‐ray photoelectron spectroscopy, Fourier transform infrared spectrum, scanning electron microscopy, transmission electron microscopy, and solid ultraviolet‐visible (UV‐vis) diffuse reflectance spectra. The Bi2 O3 /In2 O3 heterojunction exhibits a remarkable photocatalytic degradation capacity for Rhodamine B, which is better than that of pure Bi2 O3 and In2 O3 . The photogenerated charges separation and transfer process of the Bi2 O3 /In2 O3 heterojunction follows a direct Z‐scheme mechanism under UV–vis light irradiation. The trapping experiment indicates that oxidative radicals including OH, h +, and O2 − play crucial roles in the photodegradation process. The outstanding photodegradation capacity is ascribed to spatially separated charge carriers, fast‐charge transportation characteristic, and special bandgap structure of the Bi2 O3 /In2 O3 heterojunction. The introduction of H + and OH − ions into the reaction system promotes the formation of OH and O2 − radicals, significantly enhancing the photodegradation rate of RhB. This study presents a new insight into the construction of the Z‐scheme Bi2 O3 /In2 O3 heterojunction photocatalyst with potential application in wastewater treatment. Abstract : A Bi2 O3 /In2 O3 heterojunction is fabricated via a facile hydrothermal method using sodium bismuthate and indium nitrate as the source materials. The Bi2 O3 /In2 O3 heterojunction exhibits a remarkable photocatalytic degradation capacity for Rhodamine B. This study presents an insight into the construction of the Z‐scheme Bi2 O3 /In2 O3 heterojunction photocatalyst with potential application in wastewater treatment.